Recurrent squamous cell carcinoma of the lower lip: salvage surgery outcome. Issue 8 (October 2021) - Copelli, C.; Manfuso, A.; Cassano, L.; Pederneschi, N.; Tewfik, K.; Pansini, A.; Cocchi, R.
Abstract: Squamous cell carcinoma (SCC) of the lip is one of the most commonly occurring oral cancers, mainly involving the lower lip. Despite a good prognosis in cases of early detection, survival rates drop dramatically in the presence of recurrence. While there are many studies in the literature regarding the management of primary tumours, the rate of recurrence in lower lip SCC is low and therefore there are few data and articles about them. We retrospectively reviewed patients affected by recurrent SCC of the lower lip treated surgically from 2011 to 2019 in a single centre. Data and results were compared with those in the literature. A total of 16 patients (mean [range] age: 78.1 [62-93] years) were eligible for inclusion. The disease-free survival rate at 2 and 5 years was 29.6% and the overall survival rate at 2 and 5 years was 14.4%. A significantly higher rate of failure and a worse prognosis was observed in patients with neck involvement. The prognosis of recurrent lower lip SCC is unfavourable with extremely low survival rates. This issue is probably linked to the oncological pathology but also to the advanced age of most patients, the presence of several comorbidities and, consequently, the high risk of perioperative mortality. For this reason, the analysis of data sets reported in the literature may help the surgeon in the management of recurrences and selection of patients.